Analisis Tingkat Kapabilitas Knowledge Management System Information Menggunakan Model Framework Cobit 5 (Studi Kasus Hotel XYZ) - Muhamad Dody Firmansyah (ISB Atma Luhur, 2021)
Abstract - Knowledge Management System (KMS) to improve the quality of human resources in an organization by improving communication among employees and to increase skill by transferring knowledge. Knowledge Management System (KMS) is one of many ways to foster a culture of knowledge sharing among individuals and organizations. In this research, the researcher tries to develop a model of knowledge management system suitable for existing condition at the Hotel XYZ run effectively, it is necessary to conduct an evaluation activity by examining the process of managing knowledge possessed by each individual can be transferred to other individuals through the process of knowledge sharing and knowledge presentation management and through Effective management of knowledge is expected to be maintained well so that it can provide benefits to the company. KMS (Knowledge Management System) is main tool for implementation of existing processes in the knowledge management , is necessary to do an analysis to find out the extent of the processes of knowledge level management found in Hotel XYZ at the maturity level of KMS (Knowledge Management System) it affects the performance of employees, the results of the analysis can be expected to be an evaluation material that will have an impact on the company.